PENGARUH SELEBGRAM ENDORSEMENT DALAM MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PRODUK KASA BEAUTE MOIST LIP SERUM - Putri Sinta; Boma Jonaldy Tanjung (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This study aims to determine the effect of celebrity endorsement in Instagram social media on purchasing decisions for Kasa Beaute Moist Lip Serum products. This study uses a type of quantitative research with an associative approach. The population in this study were the general public with a total of 100 population. The sample of this study was 100 people using the slovin formula and obtained a sample of 54 people from the community. The technique used in this research is non probability sampling or purposive sampling method. The data source to be used is primary data. The method in collecting this data uses a survey method with a questionnaire questionnaire. The data analysis technique in this study uses descriptive statistical analysis, normality test, simple linear regression test, hypothesis testing, F test, partial effect significance test (t test), and determination coefficient test while for data processing using SPSS Statistics software version 26. The results of data analysis in this study show that the average value of problem solving in endorsement celebrities is lower than purchasing decisions. This can be seen from the difference in average values of 0.8070 and 0.8337 and the distribution of data on endorsement celebgrams is better than purchasing decisions, because the standard deviation value tends to be smaller. The hypothesis in this study, the authors used the t test with the results of the significance obtained smaller (0.000 <0.05) which means it is feasible to test. The author also uses a partial effect significance test (t test) with the results of the significance obtained smaller (0.000 <0.05) which means that the endorsement celebgram variable has a positive effect on purchasing decisions and the author also uses the coefficient of determination test with the results of the R value obtaining a value of 0.837 which means it shows the relationship between the endorsement celebgram variable and purchasing decisions there is a strong correlation